2010
DOI: 10.1093/jxb/erq069
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation kinetics of physiological and molecular responses of plants to multiple mechanical loadings

Abstract: During their development, plants are subjected to repeated and fluctuating wind loads, an environmental factor predicted to increase in importance by scenarios of global climatic change. Notwithstanding the importance of wind stress on plant growth and development, little is known about plant acclimation to the bending stresses imposed by repeated winds. The time-course of acclimation of young poplars (Populus tremula L.xP. alba L.) to multiple stem bendings is studied here by following diameter growth and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…For all of the artificial bending treatments, trees were bent once per day, on Monday, Tuesday and Wednesday during the 6 wk from 16 June 2014 to 24 July 2014 (as this sequence was shown to lead to maximal sensitivity of trees to bending by reducing accommodative desensitization, Martin et al, 2010). The trees were previously attached at the crown base with a rope that was pulled manually or with a winch.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For all of the artificial bending treatments, trees were bent once per day, on Monday, Tuesday and Wednesday during the 6 wk from 16 June 2014 to 24 July 2014 (as this sequence was shown to lead to maximal sensitivity of trees to bending by reducing accommodative desensitization, Martin et al, 2010). The trees were previously attached at the crown base with a rope that was pulled manually or with a winch.…”
Section: Researchmentioning
confidence: 99%
“…Very few reports are available on the filtering of recurrent bending deformations, all involving simplified artificial loads. It is striking, however, that Martin et al (2010), in a controlled study in poplars, observed that their young plants also filtered out a daily mechanical stimulus (after an initial 'training period').…”
mentioning
confidence: 98%
“…As soon as 1 h after the first stimulation, a second touch was less effective in inducing ACS6 expression, a gene encoding 1-aminocyclopropane-1-carboxylic acid (ACC) synthase enzyme ( Figure 1A ). In the conditions described above after the second bending of the poplar stem, about seven days without any bending stimulus were necessary to recover the full capacity for induction of gene expression ( Figure 1A , Martin et al, 2010), suggesting that this state of desensitization to mechanical loads lasts for several days. Such desenzitisation was also observed in case of the typical defensive leaf-folding reflex of Mimosa plants (Gagliano et al, 2014).…”
Section: Saturation and Desensitization Ways To Deal With Successivementioning
confidence: 96%
“…In poplar, controlled stem flexing at a sub-saturation level was coupled with kinetics analyses of the responses to each successive bending. The result was a rapid reduction in responsiveness of both radial growth and gene expression (Martin et al, 2010). In particular, these experiments showed that the second bending, 24 h after the first, was markedly weaker in inducing four early mechanoresponsive genes encoding, respectively, two calmodulins, a C2H2 transcription factor ( Figure 1A ) and a xyloglucan endotransglycosylase.…”
Section: Saturation and Desensitization Ways To Deal With Successivementioning
confidence: 99%
“…Overexpression of the PeSCL7 gene in transgenic Arabidopsis plants showed improved tolerance to drought and salt stresses (Ma et al 2010). Martin et al (2010) analyzed the mechanical stress with repeated via wind loads, and identified the zinc-finger type transcription factor ZFP2 as the bending signal inducible factor. They found increased diameter growth after the repeated bending stress.…”
Section: Stress-responsive Transcription Factors and Micrornasmentioning
confidence: 99%